2004
DOI: 10.18474/0749-8004-39.4.490
|View full text |Cite
|
Sign up to set email alerts
|

Field Response of Dendroctonus valens (Coleoptera: Scolytidae) and a Major Predator, Temnochila chlorodia (Coleoptera: Trogositidae), to Host Kairomones and a Dendroctonus spp. Pheromone Component1

Abstract: The red turpentine beetle, Dendroctonus valens (LeConte) (Coleoptera: Scolytidae), is a common bark beetle species found throughout much of North America. Aggregation pheromones have yet to be isolated and identified for D. valens. In this study, we examined the response of D. valens and a bark beetle predator, Temnochila chlorodia (Mannerheim) (Coleoptera: Trogositidae), to host produced kairomones and to the Dendroctonus spp. pheromone component exo-brevicomin. A total of 11,604 D. valens and 586 T. chlorodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 0 publications
3
18
1
Order By: Relevance
“…In general, flight periodicity agreed with descriptions provided by other authors for similar locations (Fettig et al, 2004(Fettig et al, , 2005Gaylord et al, 2006). There was a consistent trend among sites and species with more individuals collected in latespring/early-summer than in late-summer/fall (Fig.…”
Section: Ips Species and D Valens Flight Periodicitysupporting
confidence: 89%
See 2 more Smart Citations
“…In general, flight periodicity agreed with descriptions provided by other authors for similar locations (Fettig et al, 2004(Fettig et al, , 2005Gaylord et al, 2006). There was a consistent trend among sites and species with more individuals collected in latespring/early-summer than in late-summer/fall (Fig.…”
Section: Ips Species and D Valens Flight Periodicitysupporting
confidence: 89%
“…Hobson et al (1993) also reported significant increases in D. valens trap catch attributable to 3-carene and (+)-a-pinene. Combinations of these three monoterpenes are a highly effective bait in multiple-funnel traps (Fettig et al, 2004). In our study, initial quantities of a-pinene, b-pinene, 3-carene and myrcene eluting from chips were 16.9, 27.9, 23.7 and 23.9 times greater, respectively, than lopped-and-piled slash (Fig.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Responses by antennae to (R)-(+)-and (S)-())-a-pinene suggest different receptors for each enantiomer . (+)-a-Pinene, ())-b-pinene, and 3-carene are attractive in flight assays of North American populations Fettig et al 2004), but 3-carene is the best attractant in introduced populations in China (Sun et al 2004).…”
Section: Pinus Elliottii Elliottiimentioning
confidence: 99%
“…They also attack trees that are under attack by other bark beetles, such as western pine beetle (Fettig et al 2004). Attacks typically do not lead to tree mortality.…”
Section: Parameter Thinmentioning
confidence: 99%